Research Concerning the Reproduction Seasonality in Carpathian Buffalo - Stelian Sertu; Maria Voiculescu; Augustin Pop; Adrian Bota; F. Grigorie; Marcel Paraschivescu (Scientific Papers Animal Science and Biotechnologies, 2023)
Fertility in buffalo is low. That could be a question of species adaptation in new climate or a genetic trait. Scientists think buffaloes entered the South-est of Europe on two ways one with the Hune and Avar people coming trough the North of Black Sea up to the intra Charpathian Hils and a later one more prolonged  with penetratio trough Egypt, Small Asia and Greece at the time when some people migrated up to the Danube River. Buffaloes which originated from Egypt were domesticated before the ones that came through the North of Black Sea. That means in Romania there are two different buffalo populations: the Carpathian Buffalo adapted to reproduce in a cold and wet climate, outside the area of its wild ancestors and a Danube Buffalo that underwent more influence domestication apart. These two populations reproduced separately by territorial state insulation. All buffalo breeds including the ones in the native domestication area show grouped calving. The present paper has to answer if grouped calving in buffalo is due to photoperiodic exchange along the year or to the poor feeding in some seasons. The answer to this question will decide the actions needed to improve buffalo cows’ fertility.